γδT cells, a key subset of T cell for cancer immunotherapy - Lv, Jianzhen; Liu, Zheng; Ren, Xiangting; Song, Siyuan; Zhang, Yan; Wang, Yi (Frontiers in Immunology, 2025)
γδT cells represent a unique and versatile subset of T cells characterized by the expression of T-cell receptors (TCRs) composed of γ and δ chains. Unlike conventional αβT cells, γδT cells do not require major histocompatibility complex (MHC)-dependent antigen presentation for activation, enabling them to recognize and respond to a wide array of antigens, including phosphoantigens, stress-induced ligands, and tumor-associated antigens. While γδT cells are relatively rare in peripheral blood, they are enriched in peripheral tissues such as the skin, intestine, and lung. These cells play a crucial role in tumor immunotherapy by exerting direct cytotoxicity through the production of inflammatory cytokines (e.g., interferon-gamma (IFN-γ), tumor necrosis factor-alpha (TNF-α), and interleukin-17 (IL-17)) and cytotoxic molecules (e.g., perforin and granzyme). Recent advances in γδT cell research have elucidated their mechanisms of tumor recognition, including the detection of phosphoantigens and stress-induced ligands like MICA (MHC class I polypeptide-related sequence A), MICB (MHC class I polypeptide-related sequence B), and ULBP (UL16-binding protein). Furthermore, various strategies to enhance γδT cell-based tumor immunotherapy have been developed, such as in vitro expansion using phosphoantigen-based therapies, cytokine stimulation, and chimeric antigen receptor (CAR)-γδT cell engineering. These advancements have shown promising results in both preclinical and clinical settings, paving the way for γδT cells to become a powerful tool in cancer immunotherapy. This review highlights the key mechanisms, functions, and strategies to harness the potential of γδT cells for effective tumor immunotherapy.